Collaborative Management in Building a Culture of Literacy in Elementary Schools - Naris Setyowati; Endang Wuryandini; Muhtarom (Jurnal Penelitian Pendidikan IPA, 2025)
A strong literacy culture in elementary schools is built through collaborative management involving shared decision-making, strategic resource allocation, and ongoing evaluation of literacy programs among all stakeholders. By implementing collaborative management, elementary schools can systematically design and implement integrated literacy programs that empower students, transforming the learning environment into an ecosystem that values ​​reading and critical thinking. This study describes the management of the literacy program at SD Negeri 03 Kesesirejo in Pemalang Regency, which consists of four main functions planning, organizing, implementing, and monitoring and evaluation. this study aims to describe the literacy program management at SD Negeri 03 Kesesirejo, which includes four components: planning, organizing, implementing, and monitoring or controlling. The research used a descriptive qualitative approach with a case study design. Data were obtained through interviews, observations, and documentation with the principal, teachers, students, the school committee, and the community. The results indicate that program planning was carried out in a participatory manner through collaboration between all parties. Organizational processes were effective with a clear division of structures and tasks. Implementation of the literacy program was carried out through routine reading, writing, and publication of student work. Monitoring was conducted periodically to ensure program sustainability. Therefore, collaborative literacy management can foster a productive and sustainable school literacy ecosystem.